PERANCANGAN GAME EDUKASI â€œSEMANGAT SI SEMUTâ€ SEBAGAI MEDIA UNTUK MENANAMKAN SEMANGAT GOTONG ROYONG PADA ANAK USIA DINI - Sugiyanto Sugiyanto Sugiyanto; Khamadi Khamadi Khamadi (Semantik, 2011)
Globalization and the influence of foreign culture has caused a tremendous effect on the culture that had been upheld by the nation, especially the traditional culture of mutual help. In a relatively short time has turned into the properties of selfish, individualistic and indifferent nature and no longer want to care about what happens in the environment.Game a technology-based visual communications media that much-loved community, especially by children. Age of children are of age to play. With their play to develop emotional, physical and cognitive growth. By playing them develop imagination, skill, independence, creativity, and ability bersosialisasi.Semut is one of the most social groups in the genus of insects and live as a community, called